2M-SELAR: A Model for Mining Sequential Least Association Rules - Abdullah, Zailani; Omer, Adam; Tutut, Herawan; Noraziah, Ahmad; Mohd Saman, Md Yazid; Hamdan, Abdul Razak (Springer, 2019)
Recently, mining least association rule from the sequential data becomes more important in certain domain areas such as education, healthcare, text mining, etc. due to its uniqueness and usefulness. However, discovering such rule is a great challenge because it involves with a set of least items which usually holds a very low in term of support. Therefore, in this paper propose a model for mining sequential least association rule (2M-SELAR) that embedded with SELAR algorithm, and Critical Relative Support (CRS) and Definite Factor (DF) measures. The experimental results reveal that 2M-SELAR can successfully generate the desired rule from the given datasets.